Hourly non-gridded volcanic ash properties retrieved from SEVIRI measurements for the Eyjafjallajökull 2010 eruption - Kylling, Arve; Sollum, Espen (Zenodo, 2020)
- Publishing date: 14.05.2020 - Title: Hourly non-gridded volcanic ash properties retrieved from SEVIRI measurements for the Eyjafjallajökull 2010 eruption - Authors of data set: Arve Kylling (aky@nilu.no), NILU - Norwegian Institute for Air Research Espen Sollum, NILU - Norwegian Institute for Air Research - Description: Ash satellite detection and retrievals were made using infrared measurements by SEVIRI on board the MSG-2 satellite. MSG-2 is geostationary, centred at approximately 0N latitude, and has a 70 degree view coverage (Schmetz et al., 2002). Pixel resolution is 3 × 3 km at nadir, while at the edge of the coverage it increases to 10 × 10 km. Observations are available every 15 min. Pixels are identified as containing ash if the brightness temperature difference (BTD) between the SEVIRI 10.8 and 12.0 μm channels (Prata, 1989) is below a certain threshold value, here −0.5 K. The BTDs have been adjusted for water vapour absorption using the approach of Yu et al. (2002). Ash clouds give negative BTDs, ice give positive BTDs, and BTDs of water clouds are closer to zero. The ash mass loading and effective ash particle radius are retrieved as described in Kylling et al. (2015). The retrieval is based on a modification of the Bayesian optimal estimation technique used by Francis et al. (2012). We assume andesite ash with refractive index from Pollack et al. (1973), spherical ash particles, and a lognormal size distribution. The lognormal size distribution is described by the geometric mean radius and the geometric standard deviation. The data set includes retrievals for geometric standard deviation of 1.5, 1.75, 2.0, and 2.25, which is a subset of the values used by Francis et al. (2012). The data set has been used by Steensen et al. (2017). Data comes as hourly files broadly covering Iceland, Europe and the surrounding oceans. The files are in bzip2 netcdf-format which should be self-explanatory. - Version: 1.0 - Language: English - Keywords Volcanic ash, remote sensing, SEVIRI, Eyjafjallajökull 2010 - Additional notes None - Access right: Open access - License: CC BY-SA 4.0 - Funding: Partly funded by the Norwegian ash project financed by the Norwegian Ministry of Transport and Communications and Avinor. - References: Francis, P. N., Cooke, M. C., and Saunders, R.W.: Retrieval of physical properties of volcanic ash using Meteosat: A case study from the 2010 Eyjafjallajokull eruption, J. Geophys. Res. Atmos., 117, D00U09, https://doi.org/10.1029/2011JD016788, 2012. Kylling, A., Kristiansen, N., Stohl, A., Buras-Schnell, R., Emde, C., and Gasteiger, J.: A model sensitivity study of the impact of clouds on satellite detection and retrieval of volcanic ash, Atmos. Meas. Tech., 8, 1935-1949, https://doi.org/10.5194/amt-8-1935- 2015, 2015. Pollack, J. B., Toon, O. B., and Khare, B. N.: Optical properties of some terrestrial rocks and glasses, Icarus, 19, 372-389, https://doi.org/10.1016/0019-1035(73)90115-2, 1973. Prata, A. J.: Observations of volcanic ash clouds in the 10-12 um window using AVHRR/2 data, Int. J. Remote Sens., 10, 751-761, 1989. Schmetz, J., Pili, P., Tjemkes, S., and Just, D.: An introduction to Meteosat second generation (MSG), B. Am. Meteorol. Soc., 83, 977-992, 2002. Steensen, B. M., Kylling, A., Kristiansen, N. I., and Schulz, M.: Uncertainty assessment and applicability of an inversion method for volcanic ash forecasting, Atmos. Chem. Phys., 17, 9205-9222, https://doi.org/10.5194/acp-17-9205-2017, 2017. Yu, T., Rose, W. I., and Prata, A. J.: Atmospheric correction for satellite-based volcanic ash mapping and retrievals using "split window" IR data from GOES and AVHRR, J. Geophys. Res. Atmos., 107, https://doi.org/10.1029/2001JD000706, 2002.